Parasite systematics in the 21st century: opportunities and obstacles - Daniel R Brooks (Memorias do Instituto Oswaldo Cruz, 2000)
Thanks to the phylogenetic systematics revolution, systematic parasitology is poised to make significant contributions in tropical medicine and public health, biodiversity science, and evolutionary biology. At the same time, the taxonomic impediment is acute within parasitology. Both systematists and non-systematists must be interested in working towards common goals and establishing collaborative efforts in order to re-vitalize and re-populate systematic parasitology.